Low Virulence of the Fungi Escovopsis and Escovopsioides to a Leaf-Cutting Ant-Fungus Symbiosis - Mendonça, Débora Mello Furtado de; Caixeta, Marcela Cristina Silva; Martins, Gabriel Leite; Moreira, Camila Costa; Kloss, Thiago Gechel; Elliot, Simon Luke (Frontiers in Microbiology, 2021)
Eusocial insects interact with a diversity of parasites that can threaten their survival and reproduction. The amount of harm these parasites cause to their hosts (i.e. their virulence) can be influenced by numerous factors, such as the ecological context in which the parasite and its host are inserted. Leaf-cutting ants (genera Atta, Acromyrmex and Amoimyrmex, Attini: Formicidae) are an example of a eusocial insect whose colonies are constantly threatened by parasites. The fungi Escovopsis and Escovopsioides (Ascomycota: Hypocreales) are considered a highly virulent parasite and an antagonist, respectively, to the leaf-cutting ants’ fungal cultivar, Leucoagaricus gongylophorus (Basidiomycota: Agaricales). Since Escovopsis and Escovopsioides are common inhabitants of healthy colonies that can live for years, we expect them to have low levels of virulence. However, this virulence could vary depending on ecological context. We therefore tested two hypotheses: (i) Escovopsis and Escovopsioides are of low virulence to colonies; (ii) virulence increases as colony complexity decreases. For this, we used three levels of complexity: queenright colonies (fungus garden with queen and workers), queenless colonies (fungus garden and workers, without queen) and fungus gardens (without any ants). Each was inoculated with extremely high concentrations of conidia of Escovopsis moelleri, Escovopsioides nivea, the mycoparasitic fungus Trichoderma longibrachiatum or a blank control. We found that these fungi were of low virulence to queenright colonies. The survival of queenless colonies was decreased by E. moelleri and fungus gardens were suppressed by the all treatments. Moreover, E. nivea and T. longibrachiatum seemed to be less aggressive than E. moelleri, observed both in vivo and in vitro. The results highlight the importance of each element (queen, workers and fungus garden) in the leaf-cutting ants-fungus symbiosis. Most importantly, we showed that Escovopsis may not be virulent to healthy colonies, despite commonly being described as such, with the reported virulence of Escovopsis being due to poor colony conditions in the field or in laboratory experiments.